Review of Climate Change and India’s Water Supply - Dr. Gargi (International Journal of Engineering and Management Research, 2019)
Some of the predicted consequences of climate change include an increase in the frequency and severity of extreme weather events, increased monsoon variability, and the emergence of new disasters, such as sea level rise, as well as new vulnerabilities with differential spatial and socioeconomic impacts on communities. The hydrological cycle, water supply for drinking water, forests and ecosystems, losses of coastal wetlands and mangroves, food security, public health, and other associated areas are all projected to be severely impacted by this unprecedented increase. The impoverished and vulnerable sections, which make up anywhere from a quarter to half of the population in most Indian towns, would be hit the hardest. This would be especially devastating for emerging countries like India. In most of India's agro climatic regions and river basins, human activities like land use change, water uses, inter-basin transfers, cropping patterns, irrigation, and drainage are altering the hydrological cycle in both quantitative and qualitative ways. With the water table dropping, many previously secure areas are becoming vulnerable and overexploited. As a result, surface water, ground water, and the natural environment they rely on have all become increasingly important to manage sustainably in recent years. For resource planning and sustainable development to serve as a foundation for economic and social growth, it is essential to assess the availability of water resources in light of future national requirements, paying special attention to the increasing demands for water and the anticipated impacts of climate change and variability. This research examined the potential for water-related developments and the availability of surface and groundwater resources in India in light of the potential effects of climate change on this country's ability to meet future demand. Water security, community resilience, and disaster preparedness must all be addressed simultaneously, so a comprehensive strategy is needed.